Efficacy of Intense Pulsed Light in the Treatment of Recurrent Chalaziosis - Zhu, Yirui; Huang, Xiaodan; Lin, Lin; Di, Mengshu; Chen, Ruida; Dong, Jilian; Jin, Xiuming (Frontiers in Medicine, 2022)
Purpose: High recurrence rate of chalazion and serious side effects of repeated surgical excision may help increase awareness of recurrent and refractory chalazion as a serious disorder affecting many aspects of life. This present study was aimed to investigate the efficacy and safety of intense pulse light (IPL) therapy and meibomian gland expression (MGX) in cases of recurrent chalazia after excision surgery. Methods: Forty-two consecutive recurrent chalazia cases (35 patients) treated with IPL-MGX were enrolled. All patients initially underwent excision with curettage. One week after lesion excision, IPL-MGX were performed at least 3 times. Another set of age- and sex-matched consecutive cases of recurrent chalazia, who received excision with curettage, but went without IPL-MGX treatment, were collected to calculate recurrence rate. Treatment efficacy and safety were measured before IPL-MGX treatment and 1 month after the final treatment. Results: The majority of patients received 4 sessions of IPL-MGX therapy (20 patients; 57.1%) or 3 sessions of IPL-MGX therapy (10 patients; 28.6%), resulting in a lower recurrence rate of 11.4% compared to that of recurrent chalazia without IPL-MGX cases (45.6%, P < 0.001). The NIBUT was significantly prolonged from 3.9 ± 1.8 s to 5.1 ± 1.7 s at 4 weeks after the final treatment (P = 0.001). There was also an increase in the mean TMH score that was statistically significant when compared with baseline (0.17 ± 0.07 vs 0.21± 0.09; P = 0.008). Furthermore, meibum quality and expressibility scores were significantly decreased at 4 weeks after the final treatment (both P <0.001). Intraocular pressure and visual acuity remained stable after treatment. Conclusion: IPL treatment combined with MGX is safe and effective in decreasing the recurrence rate of recurrent chalazia by improving meibomian gland function. IPL-MGX may be considered as an alternative first-line treatment in recurrent or refractory cases post excision.